ECONOMIC PROSPECTS OF PORANG PLANT DEVELOPMENT IN THE PANDEMIC TIME COVID-19: Economic prospects of porang plant development in the pandemic time covid 19 - Ni Made Astuti Wahyu Utami (Universitas Islam Balitar, 2021)
Porang tubers have enormous potential in the field of production. Bali plans to export 5,000 tons of porang tubers to China this year. This need cannot be fulfilled because in Indonesia porang has not been cultivated intensively. Star fruit village is an area located at an altitude of 500 - 600 masl. Most of the people in this village work as farmers / planters. At the time of the Covid-19 pandemic, most of the villagers experienced layoffs (PHK). The objectives of this study were to identify porang cultivation at the research location; and know economic prospects of porang plant cultivation at the research location. Porang cultivation is carried out under the shade of coffee, clove, durian and mangosteen plants which are in accordance with the characteristics of the porang plant. Porang tubers are sold to pegepul in the local village for Rp. 11,000 with a tuber weight of 2-3 kg. Porang cultivation is carried out between annual crops such as coffee, cloves, mangosteen and durian. Porang is a shade tolerant plant up to 60%. So it is suitable to be cultivated in Belimbing Village which has an altitude of 500-600 meters above sea level. Porang plants have economic prospects because they have many benefits and are processed plants that are exported to various countries.